A música na cantoria: processos de transmissão musical na prática do cantador repentista - Rodrigues, Rodolfo (2022)
The repentista singing is a poetic-musical practice widely spread in the Northeast of Brazil. It is distinguished by the dexterity with which its practitioners — called cantadores — construct (improvise), through modalities and themes, the poetic-musical discourse. The acquisition of the necessary skills for the effective practice of singing occurs in processes in which I assume the form of transmission. Therefore, the objective of this research was to understand the distinct aspects of musical transmission within the scope of the repentista singing, based on a study with three singers from the state of Ceará. Due to the restrictions on social interaction that began in the first half of 2020, as a result of COVID 19, a methodology was adopted in which we call ethnography in virtual field, seeking to meet the research expectations that it had, throughout its development. , contact with the singers only through social networks and other virtual communication platforms. Based on the literature and the report of the interviewed singers, it was evidenced that the musical transmission processes occur at distinct stages and levels. In general, the first conceptions emerge with listening and/or participating in spaces where singing takes place, almost always from a singing relative, and the skills are developed in social interactions, when they stand in front of the public and act. with other singers. The “gift” is also an important aspect in this process, since its possession is an innate acquisition, presented by “something/someone superior,” which leads singers to be, effectively, good singers. Finally, the trajectories of each singer and their conceptions about the poetic-musical making were analyzed, presenting important points for the understanding of the studied phenomenon.